2020
DOI: 10.1371/journal.pone.0230337
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diagnostic and analytic performance of the SD Bioline Dengue Duo test for dengue virus (DENV) infections in an endemic area (Savannakhet province, Lao People's Democratic Republic)

Abstract: BackgroundRapid tests detecting both dengue virus (DENV) NS1 antigen and anti-DENV IgM and IgG antibodies facilitate diagnosis of dengue fever (DF) in resource-poor settings. Methodology/principal findings92 acute phase serum samples from patients with a PCR-confirmed DENV infection collected in Lao People's Democratic Republic (Lao PDR) in 2013 and 2015 were analyzed with the SD Bioline Dengue Duo test. A subset of 74 samples was additionally tested with the Platelia NS1 antigen test, the Panbio DENV μ-captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 39 publications
1
38
0
1
Order By: Relevance
“…Recently, Lustig et al (11) reported false positive results of the Euroimmun Anti-SARS-CoV-2 IgA and IgG ELISAs in sera originating from donors with acute or past dengue virus (DENV) infection. In our study, 29 (21.6%) of the 134 Colombian donors tested positive in the SD Bioline Dengue Duo IgG Rapid Test (Alere/Abbott, USA), indicating a high titer of anti-DENV IgG antibodies (15). Indeed, two of the three Colombian sera testing positive in the spike-based Euroimmun Anti-SARS-CoV-2 ELISA (but negative in the nucleoprotein-based SARS-CoV-2 ELISAs) belonged to this subgroup.…”
Section: The Studymentioning
confidence: 56%
“…Recently, Lustig et al (11) reported false positive results of the Euroimmun Anti-SARS-CoV-2 IgA and IgG ELISAs in sera originating from donors with acute or past dengue virus (DENV) infection. In our study, 29 (21.6%) of the 134 Colombian donors tested positive in the SD Bioline Dengue Duo IgG Rapid Test (Alere/Abbott, USA), indicating a high titer of anti-DENV IgG antibodies (15). Indeed, two of the three Colombian sera testing positive in the spike-based Euroimmun Anti-SARS-CoV-2 ELISA (but negative in the nucleoprotein-based SARS-CoV-2 ELISAs) belonged to this subgroup.…”
Section: The Studymentioning
confidence: 56%
“…20,22 The lower sensitivity of the NS1 RDT has also been confirmed in independent studies. 15,19,23,33…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, it is now acknowledged that the combined testing of DENV RNA and/or NS1 antigen with anti-DENV IgM and IgG serology increases the sensitivity of DENV infection diagnosis, by broadening the time window of diagnosis after onset of fever. 8,10,1519 Because RT-PCR assays are complex and costly, albeit being highly accurate, healthcare providers are turning to easy-to-use ELISA- and RDT-based assays detecting DENV NS1 antigen and anti-DENV IgM and IgG antibodies. ELISA and RDT present both pros and cons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IgM and IgG can also be falsely positive when testing for one virus in the presence of the other due to similar viral surface epitopes, which creates difficulties elucidating single versus dual infection. 49 Many commercial serological kits are available for dengue and some combine NS-1 ELISA to confer very high levels of detection of acute infection, 50 the high specificity of NS-1 ELISA for dengue virus is also highly advantageous in identifying true dengue infection. 51 Current Centers for Disease Control and Prevention (CDC) recommendations for symptomatic pregnant patients with suspected zika/dengue infection include collecting serum and urine samples within 12 weeks of onset of symptoms to test nucleic acid amplification test (NAAT) and IgM for dengue/zika.…”
Section: Denguementioning
confidence: 99%